THE STUDENTS’ DIFFICULTIES IN LEARNING READING COMPREHENSION USING NARRATIVE TEXT THROUGH WHATSSAPP - Shofi Ashma Maryam; Efransyah Efransyah (PROJECT (Professional Journal of English Education), 2021)
This research aims to find out students’ difficulties in learning reading comprehension using narrative text through whatsapp for the third grade students. In this research, the writer used qualitative research method.  To collect the data, the researchers used questionnaire and test. From the first test, results was obtained 12 of 48 students who managed to achieve KKM. While on the second test, there was an increase to 42 of 48 students who managed to reach KKM. It can be concluded that whatsapp can make it easier for teachers and students in learning reading comprehension using narrative text, especially in this pandemic covid-19. The results of questionnaire showed that the mostl influenced factor of students' difficulties in learning reading comprhension are lack of vocabulary mastery, internet network problems and family factors. Keywords:  Narrative Text, Reading Comprehension, Whatsapp